Comparison of yield by different methods of oil extraction from pequi pulp (Research, Society and Development, 2020)
The oil extracted from the pequi pulp encompasses benefits in several areas, ranging from the medical field to the production of biodiesel, in addition to being rich in carotenoids. The objective of the work was to compare different methods of oil extraction from pequi pulp, and the study of the viability of a solar concentrator as an alternative. For the extraction, a Soxhlet device, an ultrasound and a twelve-sided biangular solar concentrator were used. The pequi pulp sample was previously dried and crushed in order to optimize the extraction process. The solvents used were ethanol and hexane. When the sample was left in an oven at 60ºC for 16 hours to perform its drying, a better extraction yield was obtained. The method that obtained the best yield of extracted oil was Soxhlet using hexane as the extracting solvent (59.96%). Hexane proved to be a more suitable solvent than ethanol. It was concluded in the experiment that the solar concentrator is a good alternative for the extraction process, however it has some limitations, such as the dependence on temperature and solar radiation and the large amount of solvent it uses.